Compressive strength and splitting tensile strength of oil palm shell lightweight aggregate concrete containing coal bottom ash - Nur Liyana Hanis, Hamdan (2019)
Coal bottom ash (CBA) is a residue of coal thermal power plant. Meanwhile, oil palm shell (OPS) is a by-product of oil palm industries. Usually, both of this materials have no use towards this industries and being abandon at landfill. The increment amount of OPS and CBA lead to this research to make use of this waste product in concrete making. The replacement of river sand with industrial by-products of coal in OPS lightweight aggregate concrete can prove both technically and economically beneficial to the construction industry. In this research, laboratory tests have been conducted to find out the effect of coal bottom ash as a substitute material of river sand towards mechanical properties in lightweight aggregate concrete. River sand was substituted with coal bottom ash by mass in concrete at 0, 10, 20, and 30% replacement level. All of these specimen are subjected to air curing up to 60 days. The tests involved in this research are compressive strength test and splitting tensile strength test. The test results show that at 10% of CBA replacement give the highest reading of compressive and splitting tensile strength at all curing age. Meanwhile, partial replacement of CBA greater than 10% decrease the concrete strength.